2014
DOI: 10.1159/000356698
|View full text |Cite
|
Sign up to set email alerts
|

Association between a Lumican Promoter Polymorphism and High Myopia in the Chinese Population: A Meta-Analysis of Case-Control Studies

Abstract: Purpose: To evaluate the relationship between lumican polymorphisms and high myopia in Chinese populations. Methods: An electronic search was conducted in Pubmed, Embase, Cochrane Library and the China Biological Medicine Database for articles published prior to September 30, 2012. A meta-analysis was performed to assess heterogeneity, combine results and determine publication bias. Results: This meta-analysis, including 1,545 subjects from 5 studies, indicated that Chinese lumican rs3759223 C allele carriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…While the current study was in progress, Feng et el [29] and Deng et el [30] as well as Liao et al [31] reported similar researches concern the relationship between rs3759223 polymorphisms and high myopia. Our meta-analysis is still superior over them in some aspects even though there are some similarities between our research and those.…”
Section: Discussionsupporting
confidence: 60%
“…While the current study was in progress, Feng et el [29] and Deng et el [30] as well as Liao et al [31] reported similar researches concern the relationship between rs3759223 polymorphisms and high myopia. Our meta-analysis is still superior over them in some aspects even though there are some similarities between our research and those.…”
Section: Discussionsupporting
confidence: 60%